What's wrong with this picture: casual disregard for history in George Clooney's The Monuments Men (2014). Issue 3 (2nd July 2016) - Karlsgodt, Elizabeth Campbell
Abstract : The best historical feature films become documents in themselves and are widely accepted by scholars as sources worthy of rigorous academic analysis. Other films remain second-rate due to a combination of historical and cinematic shortcomings. George Clooney's The Monuments Men falls into the second category. This article critiques the film from a historical perspective, focusing on the broader narrative in light of current research on Nazi art looting and postwar restitution. I argue that Clooney and co-writer Grant Heslov fail the basic test of authenticity in several key ways, including a failure to situate Nazi looting within the broader seizure of Jewish assets in the Final Solution. Rather than merely dismissing this kind of mediocre production, academic experts should remain engaged in public discussions about the history that inspires feature films. The Monuments Men taps into wide public interest in the history of Nazi looting and connects directly to current restitution cases in news headlines, giving experts an opportunity to share history with general audiences. Moreover, aggressive marketing of The Monuments Men by Sony Pictures reveals an innovative online use of historical resources, but at the same time, an alarming ambition to extend creative license into educational curricula in the guise of history. In such cases, scholars will need to assess the historical value not only of feature films, but also online promotional materials that carry creative narratives from the big screen to smart phone and tablet small screens, and potentially into history classrooms.